2020
DOI: 10.3390/mi11050460
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Air Compliance Effect on Measurement of Mechanical Properties of Blood Sample Flowing in Microfluidic Channels

Abstract: Air compliance has been used effectively to stabilize fluidic instability resulting from a syringe pump. It has also been employed to measure blood viscosity under constant shearing flows. However, due to a longer time delay, it is difficult to quantify the aggregation of red blood cells (RBCs) or blood viscoelasticity. To quantify the mechanical properties of blood samples (blood viscosity, RBC aggregation, and viscoelasticity) effectively, it is necessary to quantify contributions of air compliance to dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…According to previous studies [ 23 , 30 , 38 , 39 ], based on the assumption that the time constant remained unchanged over the interface, the time constant was obtained by analysing the interface or fluid velocity and conducting a curve-fitting procedure. Previous studies reported that the flow conditions of the test fluid influence the time constant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to previous studies [ 23 , 30 , 38 , 39 ], based on the assumption that the time constant remained unchanged over the interface, the time constant was obtained by analysing the interface or fluid velocity and conducting a curve-fitting procedure. Previous studies reported that the flow conditions of the test fluid influence the time constant.…”
Section: Resultsmentioning
confidence: 99%
“…However, the compliance effect contributes significantly to the delay in the dynamic response. The air cavity inside the driving syringe caused an increase in the time constant [ 30 ]. Thus, the higher value of the time constant hindered the measurement of RBC aggregation under specific off-period flow conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Related to his other published works, Kang [9] also studied, under periodic on-off blood flows, the contributions of air compliance to the dynamic blood flows in microfluidic channels for the successful evaluation of the mechanical properties of blood samples. The author analyzed the image intensity and interface in a co-flowing channel and concluded that air cavities in the blood sample syringe contributed to delays in the transient behaviors of blood flows, hindering the quantification of RBCs' aggregation and blood viscoelasticity [9].…”
mentioning
confidence: 96%